(untitled) - Chahal, G.S. (Harrow, U.K., 2006)
l History of the development, current status and latest refinements of plant breeding l Describes breeding plans with their genetic bases l Alternate approaches for the exploitation of heterosis and population improvement elaborated with schematic diagrams l Detailed account of biometrical procedures in molecular biology for genetic analysis and improvement of quantitative traits through QTL-mapping
Thâm cứu di truyền chọn giống phân tử,Kỹ thuật di truyền phần tử trong công tác giống cây trồng,Công nghệ sinh học cây trồng
Keywords: Plant breeding.,Plant genetics.,Hạt giống